Anatomy and facies distribution of terminal lobes in ephemeral fluvial successions: Jurassic Tordillo Formation, Neuquén Basin, Argentina. Issue 5 (28th March 2020) - Coronel, Marina D.; Isla, Manuel F.; Veiga, Gonzalo D.; Mountney, Nigel P.; Colombera, Luca
Abstract: In terminal fluvial‐fan systems, characteristic proximal to distal variations in sedimentary architectures are recognized to arise from progressive downstream loss of water discharge related to both infiltration and evaporation. This work aims to elucidate downstream trends in facies and architecture across the medial and distal zones of terminal‐fan systems, which record transitions from deposits of channel elements to lobe‐like and sheet‐like elements. This is achieved via a detailed characterization of ancient ephemeral fluvial deposits of the well‐exposed Kimmeridgian Tordillo Formation (Neuquén Basin, Argentina). The fine sand‐prone and silt‐prone succession associated with the medial to distal sectors of the system has been studied to understand relationships between depositional processes and resulting architectures. Facies and architectural‐element analyses, and quantification of resulting sedimentological data at multiple scales, have been undertaken to characterize sedimentary facies, facies transitions, bed types, architectural elements and larger‐scale architectural styles. Eight bed types with distinct internal facies transitions are defined and interpreted in terms of different types of flood events. Channelized and non‐channelized architectural elements are defined based on their constituent bed types and their external geometry. The most common elements are terminal lobes, which are composite bodies within which largely unconfined sandy deposits are stacked in a compensational manner; a hierarchical arrangement of internal components is recognized. Proximal feeder‐channel avulsion events likely controlled the evolution of terminal‐lobe elements and their spatiotemporal shifts. Stratigraphic relations between architectural elements record system‐wide trends, whereby a proximal sector dominated by channel elements passes downstream via a gradational transition to a medial sector dominated by sandy terminal‐lobe elements, which in turn passes further downstream to a distal sector dominated by silty terminal lobe‐margin and fringing deposits. This work enhances current understanding of the stratigraphic record of terminal fluvial systems at multiple scales, and provides insight that can be applied to predict the facies and architectural complexity of terminal fluvial successions.